Smart Audit: The Role of AI, Risk Management, and Governance in Enhancing Audit Quality - Sugiarto; Indra Lukmana Putra; Santi Widhiyanti (Gorontalo Accounting Journal, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to auditing practices, particularly in improving audit quality. This study aims to examine the effect of AI implementation, risk management, and governance on audit quality. A quantitative approach was employed using a survey method involving 100 auditors in East Java who have implemented AI-based auditing systems. The data were collected through purposive sampling and analyzed using multiple linear regression. The results indicate that AI implementation, risk management, and governance have a positive and significant effect on audit quality. These findings suggest that AI enhances efficiency, accuracy, and auditors’ analytical capabilities in identifying risks. However, its effectiveness depends on organizational readiness, data quality, and auditor competence. Therefore, the implementation of AI in auditing should be supported by strengthened risk management, governance, and the development of auditors’ professional capabilities.